2020
DOI: 10.1007/s00442-020-04717-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity influenced gross nitrogen mineralization, microbial ammonium consumption and gross inorganic N immobilization in a grassland experiment

Abstract: Gross rates of nitrogen (N) turnover inform about the total N release and consumption. We investigated how plant diversity affects gross N mineralization, microbial ammonium (NH 4 +) consumption and gross inorganic N immobilization in grasslands via isotopic pool dilution. The field experiment included 74 plots with 1-16 plant species and 1-4 plant functional groups (legumes, grasses, tall herbs, small herbs). We determined soil pH, shoot height, root, shoot and microbial biomass, and C and N concentrations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…Nevertheless, the capability and sustainability of C sequestration are affected largely by soil nitrogen (N) availability due to the tight coupling of C and N cycles (Chen & Chen, 2021). Higher PSD generally benefits the accumulation of soil available N (Chen et al, 2021), but case studies have reported that soil N availability may increase, decrease or remain unchanged as PSD increases (Chen et al, 2021; Lama et al, 2020; Liu et al, 2021). This uncertainty confines our comprehension of the linkage between PSD and soil N dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the capability and sustainability of C sequestration are affected largely by soil nitrogen (N) availability due to the tight coupling of C and N cycles (Chen & Chen, 2021). Higher PSD generally benefits the accumulation of soil available N (Chen et al, 2021), but case studies have reported that soil N availability may increase, decrease or remain unchanged as PSD increases (Chen et al, 2021; Lama et al, 2020; Liu et al, 2021). This uncertainty confines our comprehension of the linkage between PSD and soil N dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Higher PSD would theoretically promote gross N transformations because these variables are tightly related to gross N transformations. As PSD often stimulates plant C accumulations, the C/N ratio of shoot and root would subsequently increase (Chen & Chen, 2021; Lama et al, 2020). Accordingly, increased C/N ratio of above‐ground and below‐ground detritus may decrease soil N transformations, as observed in a few studies (Lama et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies of N transformation have been conducted using measurements of net N turnover rates; however, the recently designed technique of 15N pool dilution ( Luxhøi et al, 2005 ) together with numerical models have been utilized in the measurements of gross N transformation rates ( Müller et al, 2004 ). This measurement tool has essentially proved its importance in revealing the interactive relationships between N mineralization and N immobilization, N turnover and N losses, and N forms and their availability to plants ( Zhengchao et al, 2013 ; Lama et al, 2020 ).…”
Section: Toward Eco-efficient N Managementmentioning
confidence: 99%
“…Mixed swards have a higher N use efficiency than mono-crops due to their high potential for niche differentiation and species complementarity [43]. Moreover, Lama et al [21] also showed that higher plant species richness in pastures reduced gross N mineralization, with small herb presence increasing gross N immobilization. Thus, it was hypothesized that the mixed swards would have a higher N uptake, higher NUE and lower N 2 O emissions than the LP mono-crop swards.…”
Section: Nitrous Oxide Emissions From the Swardsmentioning
confidence: 99%
“…Mixed pastures have faster growth and rapid resource acquisition rates than monoculture pastures, increasing plant productivity through increased niche complementarity and resource uptake efficiency [12]. In addition, the presence of small herbs in the pasture might increase microbial NH 4 + consumption and gross inorganic N immobilization due to increased rhizodeposition and microbial growth stimulation [21]. Accordingly, mixed pastures have a higher tendency to mitigate N 2 O emissions [7,12].…”
Section: Introductionmentioning
confidence: 99%